A new birefringent material, HfF2(IO3)2, with a large birefringence and improved overall performances achieved by the integration of functional groups. (15th January 2023) - Huang, Yu; Fang, Zhi; Yang, Bing-Ping; Zhang, Xue-Ying; Mao, Jiang-Gao
Abstract: Birefringent materials have been widely used in optical devices. An excellent birefringent material, HfF2 (IO3 )2, was rational designed and synthesized by integrating iodate and fluoride functional groups. HfF2 (IO3 )2 inherits the huge optical anisotropy of iodates and the wide energy gap of fluorides and possesses outstanding properties including a large birefringence of 0.333 and a wide energy gap of 4.11 eV (a short ultraviolet absorption cutoff edge of 253 nm), superior to the commercial birefringent crystals such as YVO4 (Δ n, 0.204 at 532 nm; E g, 3.10 eV) and TiO2 (Δ n, 0.256 at 1530 nm; E g, 3.20 eV). HfF2 (IO3 )2 also has a high thermal stability and a wide transparent spectral range, and it is non-hygroscopic. Our investigations showed that the birefringences are linearly proportional to the parallelisms and the spatial densities of the functional lone-pair groups. This work demonstrates that combining functional groups is an effective strategy for designing promising inorganic functional materials. Graphical abstract: Image, graphical abstract